(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the structural-semantic features of lexical units that mark the names of man. Attention is focused on historical and etymological basis of individual social dialecticisms. Materials used modern Ukrainian artistic texts.